Scheduled, intermittent stimulation of the thalamus reduces tics in Tourette syndrome. (August 2016) - Rossi, P. Justin; Opri, Enrico; Shute, Jonathan B.; Molina, Rene; Bowers, Dawn; Ward, Herbert; Foote, Kelly D.; Gunduz, Aysegul; Okun, Michael S.
Abstract: Introduction: Personalized, scheduled deep brain stimulation in Tourette syndrome (TS) may permit clinically meaningful tic reduction while reducing side effects and increasing battery life. Here, we evaluate scheduled DBS applied to TS at two-year follow-up. Methods: Five patients underwent bilateral centromedian thalamic (CM) region DBS. A cranially contained constant-current device delivering stimulation on a scheduled duty cycle, as opposed to the standard continuous DBS paradigm was utilized. Baseline vs. 24-month outcomes were collected and analyzed, and a responder analysis was performed. A 40% improvement in the Modified Rush Tic Rating Scale (MRTRS) total score or Yale Global Tic Severity Scale (YGTSS) total score defined a full responder. Results: Three of the 4 patients followed to 24 months reached full responder criteria and had a mean stimulation time of 1.85 h per day. One patient lost to follow-up evaluated at the last time point (month 18) was a non-responder. Patients exhibited improvements in MRTRS score beyond the improvements previously reported for the 6 month endpoint; on average, MRTRS total score was 15.6% better at 24 months than at 6 months and YGTSS total score was 14.8% better. Combining the patients into a single cohort revealed significant improvements in the MRTRS total score (−7.6 [5.64]; p  = 0.02). Conclusion: Electrical stimulation of the centromedian thalamic region in a scheduled paradigm was effective in suppressing tics, particularly phonic tics. Full responders were able to achieve the positive DBS effect with a mean of 2.3 ± 0.9 (SEM) hours of DBS per day. Highlights: We tested personalized, scheduled DBS in Tourette at 24 month time point. 75% of patients followed to 24 months had >40% reduction in MRTRS (responders). Responders improved with only 1.85 h of DBS per day on average. MRTRS score at 24 months improved beyond the 6 month endpoint. On average, MRTRS was 15.6% better at 24 mo than at 6 mo.